The study of the correlations between handgrip strength and some anthropometric characteristics of upper extremity of elite and sub-elite Olympic style weightlifting athletes - Kenan Erdağı (Physical Education of Students, 2020)
Background and Study Aim: Handgrip strength is widely used as a functionality parameter of the upper extremity and general health. The measurement of handgrip strength by dynamometry is a low cost, noninvasive method of simple applicability. The study aims to find out handgrip strength and its correlation with some anthropometric characteristics of the upper extremity and weightlifting performance of elite (international medalists) and sub-elite (national medalists) Olympic style weightlifting athletes.